Quantum vector magnetometry based on the Voigt effect - Pyragius, Tadas (2020)
Magnetism plays a fundamental role in nature existing in almost every conceivable domain of the physical world ranging from stars and planets to our brains and hearts. Some magnetic phenomena are easy to observe and measure, whilst others are small and subtle making them almost impossible to detect. Developments in precision magnetometry, utilising the quantum nature of atoms has given access to the world of small and subtle enabling the understanding of such signals as well as pushing the boundaries of knowledge of the fundamental forces of nature. In this thesis we describe theoretical and experimental methods to dispersively detect all three vector components of an external magnetic field using radio-frequency dressed alkali atoms based on the Voigt effect. To achieve this, we measure the linear birefringence of the radio frequency dressed atomic medium via polarization homodyning. This gives rise to modulated polarization signals at the first and second harmonic of the dressing frequency. The vector components of the external magnetic field are mapped onto the quadratures of these harmonics. Our scheme requires only one frequency of modulation and has a simple single axis beam geometry making it advantageous for miniature magnetic field sensors. Furthermore, we extend our Voigt effect scheme to dressed microwave spectroscopy and show that it can be used to infer the prepared state populations paving the way towards partial quantum state tomography.